(untitled) (Eurasian Journal of Engineering and Technology, 2022)
Mortar is a brittle material that breaks throughout the drying process because of its hygroscopic nature (it expands when wet and contracts when dry). Fibers embedded in the cementitious matrix improve the flexural, tensile, and fracture toughness of mortar, all while reducing the cracking breadth. In an effort to enhance these features, an attempt was made to investigate the influence of different lengths of glass fibers in cement mortar. In this study glass fibers with length 20 and 30 mm were added to improve the properties of cement mortar. The fiber volume fraction that used 0.25%, 0.5% and 0.75% with water to cement ratio of 0.33 and super plasticizer equivalent to 2.5 % of the cement weight .The samples were casted into cube molds (50×50×50) mm for compressive strength test and prismic molds (40×40×160) mm for flexural strength test. The density of the specimens was also calculated as a physical test. Total members cured for 3,14 and 28 days in water curing tank before test .Comparing of FRM with plain mixture ,the outcomes have revealed that adding glass fibers makes the material stronger and lasts longer.